TEKNOLOGI REMOTE SENSING DAN GIS UNTUK ZONASI KOMODITAS DAN KETERSEDIAAN SUMBERDAYA LAHAN - Mubekti, Mubekti; Rahmadi, A; Rintung, S (Jurnal Sains dan Teknologi Indonesia, 2006)
One aspect of the agricultural development is an information corresponding to potency and availability of land resources for both intensification and extensification. In order to derive a such information, a study on Remote Sensing and GIS Technology Application for Agro-ecological and Land Resource Zoning has been done in Agam District, West Sumatra. The aim of the study is to set up maps of agro-ecological zone and its availability for a sustain agricultural development. A brief explanation of the methodology used in the study is presented referring to FAO procedure. The step of the activities consist of secondary data compilation, field survey, spatial analysis, and mapping. All of the spatial data analysis were conducted by using GIS and Remote Sensing soft-wares, that is to say, Arc-View and ER-Mapper. Explanation of the physical environment are exposed as preliminary knowledge of the study area. The results of the land evaluation for agricultural cultivation are divided into three groups, those are (a) Food crops and vegetables, (b) food crops, vegetables and annual crops, and (c) Annual crops. Those of each group has 43,079 hectares (19.3 % of district area), 29,514 hectares (13.2 % of district area), and 56,390 hectares (25.3 % of district area) that suitable for corresponding agricultural development, respectively. The rest covering 42.21 % of the district area are not suitable for agricultural cultivation because of natural limiting factors, such as topography, soil and climate. Regarding to the existing land use, not all suitable lands are available for agriculture extension. In this evaluation, 32,009 hectares or 14.3 % of the district area are available for those of agriculture extension.